2007
DOI: 10.1159/000103663
|View full text |Cite
|
Sign up to set email alerts
|

A Radiofrequency-Assisted Minimal Blood Loss Liver Parenchyma Dissection Technique

Abstract: Background/Aims: Intraoperative blood loss is still a major concern for surgeons operating on the liver since it is associated with a significantly higher rate of postoperative complications and shorter long-term survival. An original radiofrequency (RF)-assisted minimal blood loss technique for transecting liver parenchyma is presented. Methods: In a prospective study, starting November 2001 and ending December 2005, a total of 90 RF-assisted liver resections were done. Pre-cut coagulative desiccation was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 37 publications
0
30
0
1
Order By: Relevance
“…Biliary stenosis has been associated with thermal damage of hilar bile ducts during RF-assisted major liver resections when the transection line was close to liver hilus [27]. However, the application of a ''sequential coagulatecut'' technique can effectively avoid thermal damage of functional bile ducts when the tumor was close to the hilus [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biliary stenosis has been associated with thermal damage of hilar bile ducts during RF-assisted major liver resections when the transection line was close to liver hilus [27]. However, the application of a ''sequential coagulatecut'' technique can effectively avoid thermal damage of functional bile ducts when the tumor was close to the hilus [20].…”
Section: Discussionmentioning
confidence: 99%
“…Habib et al have previously reported on the technique for RF-PT [10]. For centrally located tumors, a ''sequential coagulate-cut'' technique [20] was routinely applied in order to avoid iatrogenic injury of remnant vessels, and clamp-crushing was used occasionally when the tumor was close to important ducts. The Pringle maneuver was not used during RF-PT.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Essentially, the non-insulated tip of the electrode is used in the same way the tip of the CUSA is used. Transection of the liver parenchyma is achieved by sequential coagulate-cut cycles always under the direct visual guidance [17].…”
Section: Methodsmentioning
confidence: 99%
“…This study was designed to evaluate the feasibility of the radiofrequency (RF)-assisted sequentional ''coagulate-cut liver resection technique'' [17] in expanding the criteria for resection of large HCC in cirrhotic livers with impaired liver function and to assess the perioperative morbidity and the overall survival in these patients treated in this manner.…”
Section: Introductionmentioning
confidence: 99%
“…Milicevic et al reported that the sequential coagulate-cut, RF-assisted liver resection technique is a safe liver transection technique associated with minimal blood loss and it has facilitated tissue-sparing liver resection (Milicevic et al, 2007). Navarra reported RF-assisted liver resection (Navarra et al, 2004), in which the median resection time was 47.5 minutes (range 30-110) with median blood loss of 30 mls (range 15-992) and mean pre-operative and post-operative hemaglobin values of 13.5 g/dL (SD ± 1.7) and 11.6 g/dL (SD ± 1.4) respectively.…”
Section: Rf (Radiofrequency) Assisted Liver Resection Techniquementioning
confidence: 99%